Green Casa Duo Talaga Bestari Tangerang Cluster Design Research - Hermawan, Adhi; Wisnuadji, Sigit; Rismayadi, Hilman (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
This study aims to examine the design and development planning of the Green Casa Duo Cluster in the Talaga Bestari area, Tangerang, which is designed to meet the needs of modern housing that is environmentally friendly and in harmony with nature. With an area of ??270 hectares, this area is equipped with various facilities such as parks, schools, sports clubs, and other recreational facilities that support a healthy and harmonious life for its residents. This study analyzes the concept of housing, planning of facilities and infrastructure, and fulfillment of building technical standards based on regulations in force in Indonesia. The results of the study show that the Green Casa Duo Cluster has succeeded in integrating modern architectural elements with the natural environment, making it an ideal residential area that prioritizes comfort and quality of life.